Experimental investigation and modeling of vapor-liquid equilibria for Bi–Zn and Bi–Sn–Zn systems at 10 Pa. (September 2021) - Zhao, Weichen; Li, Yifu; Xu, Baoqiang; Yang, Hongwei
Abstract: For the Bi–Zn and Bi–Sn–Zn systems, vacuum distillation experiments were carried out at 10 Pa. The results show that the content of Zn for the Bi–Zn system in the vapor phase could reach more than 0.999 mol fraction in vacuum distillation. The VLE (vapor-liquid equilibrium) data were correlated using the Tsuboka-Katayama's modification of the Wilson equation (T-K-Wilson). The correlation showed good agreement with experimental data. Thermodynamic consistency tests of experimental data for the binary and ternary systems were presented by the Van Ness method. The results demonstrate that VLE phase diagram is reliable for predicting the process of vacuum distillation for the systems. It provides an efficient way to guide the separation and purification of crude Zn in vacuum metallurgy Highlights: Vapor-liquid equilibria of Bi–Zn and Bi–Sn–Zn systems under vacuum condition were measured. The T-K-Wilson equation was used to calculated activities of components. The experimental data for the Bi–Zn and Bi–Sn–Zn systems were correlated using the T-K-Wilson equation.